2016
DOI: 10.21037/jtd.2016.05.91
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of using omental pedicle flap over muscle flap for closure of open window thoracotomy

Abstract: Background: Open window thoracotomy (OWT) as well as its closure are challenging. Transposition of omental pedicle and muscle flaps is often performed for OWT closure; however, the better technique among the two is unknown. The purpose of this series was to evaluate the outcomes of using both omental pedicle and muscle flaps for the aforementioned closure. Results: There were 9 (33.3%) omental pedicle flap procedures and 18 (66.7%) muscle flap procedures.The rate of local recurrence after closure of OWT was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…This is in relation to the statement of Shinohara et al that "omental pedicle flap for OWT closure is the most radical surgical treatment for thoracic empyema and is used for very severe cases" (1).…”
supporting
confidence: 56%
See 3 more Smart Citations
“…This is in relation to the statement of Shinohara et al that "omental pedicle flap for OWT closure is the most radical surgical treatment for thoracic empyema and is used for very severe cases" (1).…”
supporting
confidence: 56%
“…In this sense the OWT is one of the last resorts of adequate drainage and decreasing the infection of the empyema and not infrequently in these cases a flap is needed for the obliteration of the empyema cavity (2). Following all these principles Shinohara et al achieved remarkable results to our opinion (1).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…However, flap choice is difficult and controversial. We reported the outcomes of using the omental pedicle and muscle flaps for OWT closure (1) and concluded that the omental pedicle flap was superior to the muscle flap in terms of fewer local recurrence and shorter hospital stay, although rates of success and mortality were equal.…”
mentioning
confidence: 99%